Back Cover: Dihydrogen Splitting Using Dialkylsilylene‐Based Frustrated Lewis Pairs (Chem. Asian J. 11/2017). Issue 11 (19th May 2017) - Dong, Zhaowen; Li, Zhifang; Liu, Xupeng; Yan, Chenting; Wei, Ningka; Kira, Mitsuo; Müller, Thomas
Abstract : An isolable dialkylsilylene reacts with dihydrogen in the presence of a small amount of a conventional Lewis acid (BPh3, BEt3 ) or a base (PPh3, PEt3, NPh3, NEt3 ) at low temperatures in a hydrocarbon solvent, giving the corresponding dihydrosilane in high yields. Both the silylene/Lewis acid and silylene/Lewis base pairs work as a frustrated Lewis pair (FLP) to split dihydrogen, being in accord with the amphoteric nature of the silylene. More information can be found in the Communication by Zhaowen Dong, Zhifang Li, Mitsuo Kira, Thomas Müller et al. onpage 1204 in Issue 11, 2017 (DOI:10.1002/asia.201700143 ).